Role of cancer stem-cell marker doublecortin-like kinase 1 in head and neck squamous cell carcinoma. (April 2017) - Kadletz, Lorenz; Thurnher, Dietmar; Wiebringhaus, Robert; Erovic, Boban M.; Kotowski, Ulana; Schneider, Sven; Schmid, Rainer; Kenner, Lukas; Heiduschka, Gregor
Highlights: Expression of DCLK1 is investigated in 127 head and neck cancer patients. DCLK1 leads to reduced survival in oropharyngeal but not oral squamous cell carcinoma patients. Despite being only predictive in oropharyngeal carcinoma DCLK1 is independent of an HPV infection. Inhibition of DCLK1 leads to apoptosis and is eligible for combination with irradiation in vitro. Abstract: Background: So far, no data is available on the role of the tumor stem cell marker doublecortin-like kinase 1 (DCLK1) in head and neck squamous cell carcinoma (HNSCC). The purpose of this study was to evaluate DCLK1 expression in HNSCC patients that underwent surgery and postoperative radiotherapy, and to assess its potential as a therapeutic target in vitro. Methods: We immunohistochemically stained for DCLK1 in 127 sections of HNSCC samples obtained during surgery of HNSCC patients and correlated the expression to patients' overall- and disease-free survival, as well as human papilloma virus (HPV) status. Additionally, we compared our survival data with data obtained from The Cancer Genome Atlas (TCGA). The effects of the DCLK1 inhibitor LRRK-2-in-1 on HNSCC cell lines alone and in combination with irradiation. Results: Expression of DCLK1 in 127 patients was associated with poor survival. In particular, DCLK1 expression had a significant impact on survival of oropharyngeal carcinoma patients. Specifically, DCLK1 + /HPV − patients had the worst prognosis after simultaneous assessment of DCLK1 and HPV status in comparison to the other three possible DCLK1/HPV constellations. Higher levels of DCLK1 mRNA were also associated with poor clinical outcome. Inhibition of DCLK1 in our HNSCC cell lines led to growth arrest and induction of apoptosis. The combination of DCLK1 inhibition with irradiation had a synergistic effect. Conclusion: Firstly, DCLK1 is a prognostic biomarker for shortened survival. Secondly, through inhibition of DCLK1, it may serve as a therapeutic target as well.